Evaluation of YLT method to estimate the load carrying capacity of one-way patched reinforced concrete slab under concentrated load - Kristiawan, Stefanus Adi; Basuki, Achmad; Supriyadi, Agus; Santosa, Bambang; Marwoto, Sofa (Zielona Góra: Uniwersytet Zielonogórski)
An unsaturated polyester resin (UPR) mortar was applied to repair the damage to the tension zone`s one-way reinforced concrete (RC) slabs. The load carrying capacity of the patched RC slab is of interest to justify the effectiveness of the repair. The Yield Line Theory (YLT) may be used to estimate the load carrying capacity of patched RC slabs under concentrated load. The results of the are compared with the experimental results to evaluate the validity of the method.
Keywords: load carrying capacity; one-way slab; patch repair; reinforced concrete; YLT